The Investigation of Thermodynamic Processes in Pulsed Magnets - Bartkevičius, S.; Novickij, J. (Elektronika ir Elektrotechnika, 2007)
The analysis of thermodynamic processes in pulsed coils applicable for pulsed magnetic field generation has been done. Process modelling was carried out using Matlab Simulink software. Heating influence on maximal value of generated magnetic field and available coil failure are evaluated. The model was applied for numerical simulation of transient processes took place in pulsed coils generating magnetic fields in order of 50-70 T. It was found that overheating of wire wound coil can damage interlayer insulation led to further coil failure. The numerical simulation of pulsed currents, magnetic field and temperature rise were done for different pulsed coil constructions generated equivalent magnetic field using the same experimental equipment. Recommendations to protect pulsed coils against overheating by the increase of thermal capacity were offered. Applied model was verified experimentally and acceptable compliance of experimental and numerically simulated results was achieved. Ill. 4, bibl. 10 (in English; summaries in English, Russian and Lithuanian).